Understanding Internet Banking Motivations among Customers: A Study of Banking Marketing Management - Lelo Sintani; Fauzan Manafi AlBar; Eka Hendrayani; Ayurisya Dominata; Pandu Adi Cakranegara (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This business study aimed to discuss the motivation of bank customers to choose Internet Banking. We believe that customers choose internet banking for various reasons and motivations, so most bank service users switch to the Internet service system. We do the proof and discussion by obtaining supporting data from various sources of data information such as books and other scientific data. Before completing the discussion, it goes through an in-depth analysis process and accurate data hypotheses to get a valid answer. Based on the study and discussion, we can conclude that the motivation of customers to choose internet bank services includes convenience, cost-effective, flexible transactions, and following the technological era where services are getting more accessible, cheaper, and faster. It is hoped that this will be important for further studies.